Diet Rich in Animal Protein Promotes Pro-inflammatory Macrophage Response and Exacerbates Colitis in Mice - Kostovcikova, Klara; Coufal, Stepan; Galanova, Natalie; Fajstova, Alena; Hudcovic, Tomas; Kostovcik, Martin; Prochazkova, Petra; Jiraskova Zakostelska, Zuzana; Cermakova, Martina; Sediva, Blanka; Kuzma, Marek; Tlaskalova-Hogenova, Helena; et al. (Frontiers in Immunology, 2019)
Diet is a major factor determining gut microbiota composition and perturbances in this complex ecosystem are associated with the inflammatory bowel disease (IBD). Here, we used gnotobiotic approach to analyze, how interaction between diet rich in proteins and gut microbiota influences the sensitivity to intestinal inflammation in murine model of ulcerative colitis. We found that diet rich in animal protein (aHPD) exacerbate acute dextran sulfate sodium (DSS)-induced colitis while diet rich in plant protein (pHPD) does not. The deleterious effect of aHPD was also apparent in chronic DSS colitis and was associated with distinct changes in gut bacteria and fungi. Therefore, we induced acute DSS-colitis in germ-free mice and transferred gut microbiota from aCD or aHPD fed mice to find that this effect requires presence of microbes and aHPD at the same time. The aHPD did not change the number of regulatory T cells or Th17 cells and still worsened the colitis in immuno-deficient RAG2 knock-out mice suggesting that this effect was not dependent on adaptive immunity. The proinflammatory effect of aHPD was, however, abrogated when splenic macrophages were depleted with clodronate liposomes. This treatment prevented aHPD induced increase in colonic Ly-6Chigh pro-inflammatory monocytes, but the ration of resident Ly-6C-/low macrophages was not changed. These data show that the interactions between dietary protein of animal origin and gut microbiota increases sensitivity to intestinal inflammation by promoting pro-inflammatory response of monocytes.